Effectiveness of the PLISSIT-based Counseling on sexual function of women - Rostamkhani, Fatemeh; Ozgoli, Giti; Merghati Khoei, Efat; Jafari, Fatemeh; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Sexual dysfunction is common among women. It affects on all aspects of women’s life. Majority of these problems can be treated in early stages with counseling and a few numbers of them need to be treated by specialists. The aim of this study was to assess the effectiveness of PLISSIT-based counseling model on sexual function of women. Methods: This was a randomized clinical trial study. It was conducted in an urban health center in Zanjan. Eighty women who were married in the previous 5 years, and had sexual problems, randomly assigned to control and experimental groups. The experimental group received consultation based on PLISSIT model (Permission-limited Information-Specific Suggestion- Intensive Therapy) by a trained midwife and the control group received routine sexual consultation. Demographic and obstetric information were gathered through standard questionnaire. FSFI (Female Sexual Function Index) questionnaire were used for assessing sexual function. Data were collected from participants at three points: before consultation, 2weeks and 4weeks after consultation. Mann-Whitney, T-tests and x 2 used for data analysis. Results: Mean scores of sexual function were 25.3 before consultation, 28.8 two weeks after and 29.4 four weeks after consultation in experimental group. These differences were statistically significant (p<0.001 and p<0.001 respectively). In control group, mean scores of sexual function were 24.48, 24.44, 23.74 before, 2 weeks, 4 weeks after consultation respectively. These differences were not statistically significant (p=0.946 and p=0.375). There was no significant difference in mean score of sexual function between control and experimental groups before intervention (p=0.408). However 2 weeks and 4 weeks after the consultation this difference was significant (p<0.001 and p<0.001 respectively). Conclusion: Based on the result of this study, we can claim that sexual problem in women decreased by using the PLISSIT model. Using the PLISSIT model is recommended in health care setting. Keyword: sexual responses, consultation, PLISSIT model, sexual function Corresponding Author : Giti Ozgoli, Department of Reproductive Health and Midwifery (Second Floor), Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Science, Vali-Asr Avenue, Cross of Vali-Asr and Neiaiesh Highway, Opposite to Rajaee Heart Hospital, Tehran, Iran; REFERENCES -Anise B et al (2005). [Sexual changes and related sexual factors in primipara mothers during 3 to 6 months postpartum]. Iran Journal of Nursing. 18 (41-42) 69-75. (Persian) - Arman S Fahami F Hassan Zahraee R (2005). A comparative study on women`s sexual functioning disorders before and after menopause. Arak Medical University Journal (AMUL). 8 (3) 1- 7. (Persian) -Ayaz S Kubilay G (2008). Effectiveness of the PLISSIT model for solving the sexual problems of patients with stoma. Journal of Clinical Nursing. 18 (1) 89-98. -Bakouei F Omidvar Sh, Nasiri F (2007). [Prevalence of female sexual dysfunction in married women and its related factors in Babol]. Journal of Babol University of Medical Sciences. 9 (4) 59-64. (Persian) -Berek J S (2006). Berek and Novak`s Gynecology. 14 th edition. Philadelphia, Lippincott Williams & Wilkins. -Bolourian Z Ghanjloo J (2007). [Evaluating sexual dysfunction and some related factors in women attending Sabzevar health care centers]. Journal of Reproduction & Fertility. 8 (2) 163-170. (Persian) -Meston CM (2003). Validation of Female Sexual Function Index (FSFI) in the women with female orgasmic disorder and in women with hypoactive sexual desire disorder. Journal of sex & Marital Therapy. 29 (1) 39 - 49. -Eileen NP Harvey JH (1985). Enhancing marital sexuality: An evaluation of a program for the sexual enrichment of normal couples. Journal of Sex &Marital Therapy. 11 (3) 157-164. -Esmail S et al (2001).Sexuality and disaility: The role of health care professionals in providing options and alternatives for couples. Sexuality and Disability. 19 (4) 276-282. -Gibbs RS et al (2008). Danforth’s Obstetrics and Gynecology.10 th edition. Philadelphia, Lippincott Williams & Wilkins. -Sadock BJ, Kaplan HI, Sadock VA (2007). Kaplan & Sadock’s Synopsis of Psychiatry: Behavior Sciences/ Clinical Psychiatry.10 th edition. Philadelphia. Lippincott, Williams and Wilkins. -Lee JT Yen HW (2007). Randomized controlled evaluation of a theory-based postpartum sexual health education program. Journal of Advanced Nursing. 60 (4) 389 - 401. - Maclaren A et al (1995). Comprehensive sexual health assessment. Journal of Nurse-Midwifery. 40 (2):104 -119. -Mehrabi F Dadfar M (2003). [The role of psychological factors in sexual functional disorders]. Iranian Journal of Psychiatry and Cliical Psychology. 9 (1) 4 -11. (Persian) -Mohammadi Kh Hedari M Faghihzadeh S (2008). [The Female Sexual Function Index (FSFI); Validation of the Iranian version]. Payesh. 7 (3) 269 - 278. (Persian) -Oksuz E Malhan S (2006). Prevalence and risk factors for female sexual dysfunction in Turkish women.The Journal of Urology. 175 (2) 654 - 658 - Pakgohar M et al (2008). Effect of counseling on sexual satisfaction among hnfertile women referred to Tehran Fertility Center. Journal of Faculty of Nursing and Midwifery, Tehran University of Medical Sciences Hayat. 14 (1) 21- 30. (Persian) -Refaie-Shirpak Kh Eftekhar H Mohammad K (2007). [Incorporation of a sex education program in health care centers in Tehran]. Payesh. 6 (3) 243 - 256. (Persian) -Refaie Shirpak Kh Chinichian M Eftekhar H (2010). Need assessment: Sexual health education in family planning centers of Tehran. Payesh. 9 (3) 251-260. (Persian) -Sattarzadeh N et al (2006).[The comparison between sexual satisfaction in fertile and infertile couple referring to educational center of Alzahra in Tabriz] .Nursing Midwifery Journal Tabriz University of Medical Sciences. 2 (5) 47 - 56. (Persian) -Vural BK Temel AB (2009). Effectiveness of premarital counseling program on sexual satisfaction of recently married couples. Journal of Sexual Health. 6 (3) 222 - 232. -Wiegel M Meston C Rozen R (2005). The female sexual function index (FSFI): Cross validation and development of clinical cutoff scores. Journal of sex and Marital Therapy. 31 (1) 1-20